Effect of Ethyl Acetate and n-Butanol Fractions of Sonneratia caseolaris L.: Reducing Cholesterol Levels in Vitro - Utami, Aditya P.; Prahasiwi, Masitoh S.; Indriyanti , Erwin; Anggoro, Aloysius B.; Wijayanti, Ifa R.; Rahman, Abdul (Universitas Tadulako, 2025)
Hypercholesterolemia is an elevated condition of cholesterol levels in the blood above normal limits. Traditionally, Red Pidada plants (Sonneratia caseolaris L.) have been used as anti-hypercholesterolemic agents. This research aimed to determine the maximum concentrations, effects, and differences of the ethyl acetate and n-butanol fractions of Red Pidada rind in an in vitro study, using cholesterol activity as the endpoint; preliminary tests included phytochemical screening and TLC. Cholesterol levels were analysed using the Zak method at 468 nm. The results of the phytochemical screening and TLC were positive for flavonoids, phenolics, saponins, steroids, and tannins in the extract, ethyl acetate, and n-butanol fractions. Phytochemical screening and TLC show the presence of flavonoids, phenolics, saponins, steroids, and tannins in the extract, ethyl acetate, and n-butanol fractions. The maximum concentration of the ethyl acetate and n-butanol fraction that might decrease cholesterol levels was 300 ppm, with 62.40% ethyl acetate and 57.38% n-butanol. Data analysis using two-way ANOVA showed a significant effect (P>0.05), indicating that the ethyl acetate and n-butanol fractions lowered cholesterol levels. The post hoc test also showed a significant difference (P<0.05) between the ethyl acetate and n-butanol fraction groups.